Stimulant Medications Decrease Concussion Incidence and Some Postconcussion Neurocognitive Declines in Youth Athletes With Attention-Deficit Hyperactivity Disorder: A Critically Appraised Paper - Ashley L. Santo; Sara A. Butz; Jaymie M. Lightbourne (International Journal of Athletic Therapy and Training, 2026)
Focused Clinical Question : In youth athletes, does taking a stimulant medication for the treatment of Attention-Deficit Hyperactivity Disorder (ADHD), compared with not taking a stimulant medication, affect incidence of concussion and postconcussion recovery? Clinical Bottom Line: Athletes with ADHD taking stimulant medication have a reduced incidence of concussion compared with their peers. Athletes with ADHD taking stimulant medications performed similarly on neurocognitive assessments initially postinjury but had less neurocognitive declines approximately 1-week postinjury compared with their peers. The Level of Evidence is 3. The Grade of Recommendation is C.